1990
DOI: 10.21273/jashs.115.6.1000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Characters for Ascertaining Salt Stress Responses in Lycopersicon Species

Abstract: Plant height; stem thickness; fresh and dry weights of leaves and stems; numbers of leaves, trusses, flowers, and fruits; and leaf concentrations of Cl, Na, N-NO3, K, Ca, and Mg were measured in mature plants from 39 tomato accessions representing five species of Lycopersicon [L. esculentum Mill., L. peruvianum (L.) Mill., L. pimpinellifoliurn (Jusl.) Mill., L. hirsutum H. &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 11 publications
2
19
1
Order By: Relevance
“…The reduction of shoot expansion even at the 7.6 dS-m' 1 salt level contrasted observations on other tomato genotypes (Mitchell et al, 1991;Shannon et al, 1987), which have shown enhanced growth and yield under comparable saline conditions. In contrast to Cruz et al (1990), who found shoot length one of the most reliable response indicators for a wide range of tomato genotypes under saline stress, there was no consistent change in this parameter for 'Micro-Tom' as salinity levels increased. This lack of response is probably due to the highly compact growth habit of this selection.…”
Section: Introductioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The reduction of shoot expansion even at the 7.6 dS-m' 1 salt level contrasted observations on other tomato genotypes (Mitchell et al, 1991;Shannon et al, 1987), which have shown enhanced growth and yield under comparable saline conditions. In contrast to Cruz et al (1990), who found shoot length one of the most reliable response indicators for a wide range of tomato genotypes under saline stress, there was no consistent change in this parameter for 'Micro-Tom' as salinity levels increased. This lack of response is probably due to the highly compact growth habit of this selection.…”
Section: Introductioncontrasting
confidence: 88%
“…Numerous criteria have been used to rank salinity tolerance of members of the genus Lycopersicon (including the cultivated tomato) (Hassan and Desouki, 1982;Sacher et al, 1983;Shannon et al, 1987;Tal and Shannon, 1983). Plants exhibit a complex range of responses and resistance to stress and standard measurement parameters for one genotype may not reflect tolerance of others (Cruz et al, 1990). In addition, environmental interference can mask important traits (Epstein, 1983;McCue and Hanson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit yield reductions were due to both fruit weight and fruit number decreases in a similar proportion. Shoot development showed high reductions with salt all along the salinity range treated here; it is then a sensitive parameter to salt that could be used to evaluate salt tolerance in tomato (Cruz et al, 1990). However, the root biomass was very much less affected than the shoot and fruit yield under high salinity, indicating a preference of the root to the shoot growth as salinity increases between the range tried in this work.…”
Section: Salt Tolerancementioning
confidence: 69%
“…The main reason for this being the complex nature of salt stress and the non-availability of simpler, quicker and reliable criteria for selection of tolerant types. Therefore, efforts were directed towards development of simpler and quicker systems and evaluation of traits that characterise salt stress responses (Cruz et al 1990). In our study, efforts were made to identify such traits.…”
Section: Resultsmentioning
confidence: 99%